Fahrenheit 451 - Bradbury, Ray, 1920- (New York : Ballantine Books, 1982)
A totalitarian regime has ordered all books to be destroyed, but one of the book burners suddenly realizes their merit.
"A Del Rey book."
890
Accelerated Reader AR
Keywords: Books and reading -- Fiction; Short stories; Science fiction